EphA2 phosphorylates NLRP3 and inhibits inflammasomes in airway epithelial cells. (30th April 2020) - Zhang, Ao; Xing, Junji; Xia, Tianliang; Zhang, Hua; Fang, Mingli; Li, Shibing; Du, Yong; Li, Xian C; Zhang, Zhiqiang; Zeng, Mu‐Sheng
Abstract: Inflammasomes are intracellular complexes that form in the cytosol of inflammatory cells. NLRP3 is one of the sensor proteins in the complex that can recognize a wide variety of stimuli ranging from microbial components to environmental particulates. Here, we report that in mouse airway epithelial cells (AECs), inflammasome activation is inhibited by EphA2, a member of the transmembrane tyrosine kinase receptor family, via tyrosine phosphorylation of NLRP3 in a model of reovirus infection. We find that EphA2 depletion markedly enhances interleukin‐1β (IL‐1β) and interleukin‐18 (IL‐18) production in response to the virus. EphA2 −/− mice show stronger inflammatory infiltration and enhanced inflammasome activation upon viral infection, and aggravated asthma symptoms upon ovalbumin (ova) induction. Mechanistically, EphA2 binds to NLRP3 and induces its phosphorylation at Tyr132, thereby interfering with ASC speck formation and blocking the activation of the NLRP3‐inflammasome. These data demonstrate that reovirus employs EphA2 to suppress inflammasome activation in AECs and that EphA2 deficiency causes a pathological exacerbation of asthma in an ova‐induced asthma model. Synopsis: The tyrosine kinase receptor EphA2 functions as a negative regulator of inflammasome activation upon reovirus infection by targeting NLRP3 in airway epithelia. EphA2 also suppresses inflammatory responses in a murine ova‐induced asthma model. EphA2 knockout mice show enhanced inflammation upon viral infection in airway epithelial cells. Depletion of EphA2 promotes inflammasome activation upon infection and aggravates ovalbumin‐induced asthma. EphA2 binds to NLRP3 and induces its phosphorylation, thereby blocking inflammasome assembly and activation. Abstract : The tyrosine kinase receptor EphA2 functions as a negative regulator of inflammasome activation upon reovirus infection by targeting NLRP3 in airway epithelia. EphA2 also suppresses inflammatory responses in a murine ova‐induced asthma model.